Smart HygineMate Hub: A Smart Vending Machine - Prof. Amol T. Take; Sudipta Mondal; Nilesh Musale; Sanjana Sawant; Manasi Singh (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Activists and groups concerned with women’s health and hygiene as well as news articles, social media, and discussions have brought attention to the issue of sanitary pads selling machines. The need of convenient access to sanitary pads through vending machines particularly in public locations like schools, colleges, airports, hotels and public restrooms, was made more widely known through the efforts of Women’s Rights Organization, Non-Governmental Organizations (NGOs) and Government Initiatives. As a part of larger discussion surrounding menstrual hygiene and women’s empowerment this topic attracted attention. By automating inventory management, providing touchless interactions, various payment modes and enhancing security, the model provides a streamlined user experience. This technology also yields a valuable data insight, reduced maintenance efforts and facilitates personalized user profiles. Ultimately it contributes in improving menstrual hygiene and accessibility. The lack of scanner which makes it difficult for people in need of sanitary pads in emergencies, the difficulty of promptly monitoring and replenishing the machines, sanitary pads supply are the two of the main issues with the existing sanitary pad vending machines. Additionally consistent resources and work are needed to maintain and keep sanitary pad vending machines operational. Further issue still exists of affordability of the vending machines particularly in the rural areas due to limited resources. These issues mainly attracted to work and research on making a vending machine which will be cost effective, simplified and user-friendly machines with the use of edge cutting technologies.